2015
DOI: 10.1208/s12248-015-9844-3
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Modelling and Docking Simulations for the Discovery of Selective GPER Ligands

Abstract: Abstract. Estrogens influence multiple physiological processes and are implicated in many diseases as well. Cellular responses to estrogens are mainly mediated by the estrogen receptors (ER)α and ERβ, which act as ligand-activated transcription factors. Recently, a member of the G proteincoupled receptor (GPCR) superfamily, namely GPER/GPR30, has been identified as a further mediator of estrogen signalling in different pathophysiological conditions, including cancer. Today, computational methods are commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
1
29
0
1
Order By: Relevance
“…The selectivity studies show that CIMBA and 21 M. While CIMBA 21 displays binding to M. These results are not surprising because the molecular modeling studies on GPER and the classical ER from our group and others are in agreement that estrogenic compounds bind within a similar binding pocket as each other (33,34,(44)(45)(46)(47). Due to the proposed similarity between the binding pockets for these three receptors, it is not surprising to observe off-target 24 binding by some GPER ligands at high concentrations (16)(17)(18).…”
Section: Discussionsupporting
confidence: 65%
“…The selectivity studies show that CIMBA and 21 M. While CIMBA 21 displays binding to M. These results are not surprising because the molecular modeling studies on GPER and the classical ER from our group and others are in agreement that estrogenic compounds bind within a similar binding pocket as each other (33,34,(44)(45)(46)(47). Due to the proposed similarity between the binding pockets for these three receptors, it is not surprising to observe off-target 24 binding by some GPER ligands at high concentrations (16)(17)(18).…”
Section: Discussionsupporting
confidence: 65%
“…We have shown that the heptatransmembrane G protein-coupled estrogen receptor (GPER) was functionally and physically targeted by the peptide, which triggers an inverse agonist action [17,19,20]. Following a modeling approach, the N-terminal PLMI motif of the peptide ERα17p seems to engulf within a cavity located in the extracellular part of the GPER [17], where other ligands such as the quinoleins G-1 and G-15 and the benzopyrroloxazine PBX-2 interact [21][22][23]. Its mechanism of action refers to a pharmacological process through which it induces a proteasome-dependent decrease of GPER protein levels and abrogates the activation of (i) the epidermal growth factor receptor (EGFR), (ii) the extracellular signal-regulated kinase ERK1/2, and (iii) the transcription factor c-fos [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both components have been the subject of intensive research and development in both academic and commercial settings. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Nonetheless, computational methods for pose prediction and affinity ranking have yet to fulfill their perceived promise, as neither is yet fully reliable. [45][46][47][48][49][50][51] In fact, it is surprisingly difficult even to compare the reliability of various methods in a consistent manner, and this limitation makes it correspondingly difficult to make and verify technical progress.…”
Section: Introductionmentioning
confidence: 99%